Transdermal administration of herbal essential oil alleviates high-fat diet-induced obesity by regulating metabolism and gut microbiota - Ye, Zu-Wen; Yang, Qi-Yue; Yang, Dong-Hua; Lin, Qiao-Hong; Liu, Xiao-Xia; Li, Feng-Qin; Yan, Fang-Fang; Luo, Ping; Qin, Si; Wang, Fang (Frontiers in Pharmacology, 2025)
IntroductionObesity, a global health challenge, is characterized by excessive fat accumulation and associated metabolic disorders. The ZhiZhu decoction, a traditional Chinese herbal formula consisting of Citrus aurantium L. (ZS, ZhiShi in Chinese) and Atractylodes macrocephala Koidz (BZ, Baizhu in Chinese), is widely recognized in clinics for its gastrointestinal regulatory effects.MethodsThe chemical composition of ZS-BZ essential oil (ZBEO) was characterized using gas chromatography-mass spectrometry (GC-MS). Concurrently, we conducted in vitro investigations using HepG2 hepatoma cells to evaluate its anti-lipid deposition potential. To further elucidate the anti-obesity mechanisms, an in vivo model was established through high-fat diet (HFD)-induced obese rats, followed by transdermal ZBEO administration. Systemic analyses were performed integrating serum metabolomic profiling via UPLC-QTOF-MS and gut microbiota dynamics assessment through 16S rRNA gene sequencing.ResultsZBEO, rich in atractylon, D-limonene, and γ-elemene and shown to reduce lipid accumulation. Transdermal ZBEO administration in obese rats led to significant weight loss and improved serum metabolic indexes related to the POMC/CART signaling pathway. Additionally, ZBEO altered gut microbiota, enhancing beneficial bacteria and affecting metabolic pathways linked to obesity.DiscussionWe discovered that ZBEO exerts a significant influence on obesity by modulating key biological processes, including glucose metabolism, lipid metabolism, and the composition of gut microbiota.